Programa de educação permanente em saúde para a equipe de enfermagem da UTI adulto: cuidado ao paciente no pós-operatório de cirurgia cardíaca - Reisdorfer, Ariele Priebe (Universidade do Vale do Rio dos Sinos, 2016)
The cardiac surgery is indicated as a treatment for cardiovascular diseases. This procedure is complex and its recuperation on the immediate postoperative and a part of the mediate postoperative is realized on the Intensive Care Unit (ICU). The nursing assistance contributes for the patient recovery after cardiac surgery. The objective of this search is to prepare a Health Permanent Education Program for the nursing team that work at the ICU Adult of this hospital, about the assistance to the patient that realized cardiac surgery. The study is qualitative and twenty-seven people from the nursing team that care of this patient participated of the search. It was utilized a semi structured interview to collect data. The analysis of the data were realized through the thematic analysis. Four categories emerged from the study: team challenges for specifically providing care on the postoperative of cardiac surgery; the fear of the patient admission on the ICU; multi professional relationships and necessity of health permanent education. This study indicated that the new professionals face difficulties to care of the patient that realized this surgery. The professionals that work for longer at this place observe the fragilities on the new coworkers and also remember their difficulties when they started to work. All of them related that is necessary to qualify their professional practice. Therefore, the proposal of this study were the elaboration of the Health Permanent Education Program; a guidance booklet about the care on the postoperative of cardiac surgery; and a checklist to guide the shift change from the surgical ward to the ICU.
Keywords: Pós-operatório de cirurgia cardíaca; Unidade de terapia intensiva; Educação permanente em saúde; Equipe de enfermagem; Postoperative of cardiac surgery; Intensive care unit; Health permanent education; Nursing team; ACCNPQ::Ciências da Saúde::Enfermagem